Algorithm of the fast realization the sequential calculation - Гамаюн, В. П. (Problems of Informatization and Control, 2007)
The algorithm of the fast realization calculation is proposed. For set of calculating procedure with division bit processing is proposed. Fasting calculation is result of using position or no position data representation